PENINGKATAN PENGETAHUAN DAN SIKAP MASYARAKAT MENGENAI PENCEGAHAN COVID-19 MELALUI PELATIHAN DAVID (DAMAI BERSAMA COVID) DI DESA SUMERTA KAJA KECAMATAN DENPASAR TIMUR - Manangkot, M.V.; Juniartha, I.G.N.; Sanjiwani, I.A.; Raya, N.A.J. (Buletin Udayana Mengabdi; Vol 21 No 3 (2022): Buletin Udayana MengabdiDO - 10.24843/BUM.2022.v21.i03.p09, 2022)
Covid-19 is a disease caused by the Sars-CoV-2 coronavirus. Exposure to Covid-19 has the risk of causing respiratory function failure which has a fatal impact and death. The purpose of this activity is to increase community knowledge and attitudes regarding the prevention of Covid-19 so as to reduce the risk of the community contracting this disease. The method of this activity is face-to-face training which be held on October 22, 2021 in Sumerta Kaja Village, East Denpasar. The information was given by two speakers, namely internal medicine specialist and nursing lecturer. The information provided included knowledge about Covid-19, hand washing techniques, techniques for using and removing masks, and all about home cleaning techniques after self-isolation. The result of this activity is an increase in community knowledge and attitudes about Covid-19 prevention after participating in this activity. Conclusion and implication are the community is expected to continue to maintain and even increase vigilance against Covid-19 and can be a source of information for their families at home.   Keywords: Covid-19, prevention, knowledge, training, attitude